Індик і геловін - Silvano, Wendi, 1962- (Боокчеф, 2023)
Everyone loves Halloween candy--even Turkey. But how can he and his barnyard friends get any when the farmers only give it out to children? With a costume, of course! As his pals look on, Turkey comes up with one clever costume after another. Each trick gets better and better...but will Turkey and his friends end up with any treats?